The Legal Discourse of the State of Emergency: A Paradigm of Risk - Chavarría, Stuart Daniel (2025)
In this research, the paradigm of the atomic bomb is used as an example to understand the changes in sociopolitical and economic dynamics caused by the emergence of imperceptible, self-threatening, and universal risks. This paradigm is utilized to demonstrate the foundation and operationalization of the state of exception under a legal discourse that employs scientific criteria as a mechanism of truth in governmental practice during exceptions. This relationship shows how risk serves as a paradigm to understand the attenuations and changes of the state of exception in Costa Rica, with respect to its scope of application and the exceptional powers of the Executive.